Regional analysis of electrification: Potential for expansion in South Asia - Ag Water Solutions, Inc. (International Water Management Institute, 2012)
South Asia (SA), including India, Pakistan, Bangladesh, Sri Lanka, Nepal, and Bhutan, is one of the most populous regions in the world. Agriculture is the backbone of the economies of SA nations and is the main source of livelihood for many rural poor households. While parts of SA have experienced considerable agricultural sector growth in the last half-century, many other regions, including large parts of eastern India and Bangladesh, have lagged behind. Many farmers face water scarcity due to both physical constraints as well as lack of adequate water storage and management.